Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


after adding all the values , we get -x+12
0 0 0
(X+2) (x+3)+(x-3) (x-2)-2x(x+1)=0 (X^+3x+2x+6)+(x^-2x-3x+6)-2x^-2x=0 X^+3x+2x+6+x^-2x-3x+6-2x^-2x=0 X^+x^-2x^+3x+2x-2x-3x-2x+6+6-2=0 2X^-2x^+5x-5x-2x+12=0 -2x+12=0 -2x=-12 X=12/2 Therefore X=6 ans (^ this singh is square )
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts